DIALEKTIKA KONSTRUKSI EPISTEMOLOGI ILMU PERSPEKTIF NALAR ISLAM DAN NALAR BARAT - Ahmad Munirul Hakim; Umi Ni'matin Choiriyah (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
In the Western paradigm, science focuses more on the fundamental foundations of rationalism and empiricism. Conversely, in the Islamic tradition, science stems from three epistemologies famously associated with the thought of Abid Al-Jabiri, namely bayani, irfani, and burhani reasoning. This article aims to engage in a dialogue between Islamic and Western epistemologies within a scientific context, with a view to identifying appropriate conceptual frameworks within the epistemological framework. The approach adopted in this article employs a qualitative method based on library research. The data sources in this article are philosophical works and research that specifically discuss Islamic and Western epistemology. Additionally, sources include books, texts, and journals related to Islamic and Western epistemology. The analysis in this article employs content analysis techniques. The results indicate that the Western epistemological paradigm, which is grounded in reason and empiricism, can in fact be harmonised with Islamic epistemology. This epistemological harmony is achieved by establishing Islamic science as the primary paradigm, namely a scientific epistemological framework based on the foundations of revelation, namely the Qur’an and the Hadith. This represents an ideal, integrative epistemology for the future.